The Effectiveness of Tripartite Reading strategy in Improving Reading Comprehension and Motivation among 9th Grade Female Students in Al- Mafraq - Al- bari, Rudina Ali Jazi (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the effect of the triple reading strategy on improving the reading comprehension skills and motivation of the ninth grade female students in Mafraq. It consisted of (19) female students, who were taught by the triple reading strategy, and a control group; It consisted of (19) female students, who were taught using the usual strategy, and a reading comprehension test and a motivation scale were prepared, the validity and reliability of which were verified. The results of the study showed that there was a statistically significant effect on reading comprehension at the level of significance (α≤ 0.05) in favor of the experimental group, and the results showed that there was no statistically significant effect on the students’ motivation towards learning at the level of significance (α≤ 0.05). In light of the previous results, the study reached several recommendations, the most important of which are: Conducting more studies to reveal the effect of using triple reading in teaching Arabic language skills in the basic stage.